Characterization and kinetic modeling for pyrolytic conversion of cotton stalks. Issue 10 (15th August 2021) - Fawzy, Samer; Osman, Ahmed I.; Farrell, Charlie; Al‐Muhtaseb, Ala'a H.; Harrison, John; Al‐Fatesh, Ahmed S.; Fakeeha, Anis H.; Doran, John; Yang, Haiping; Rooney, David W.
Abstract: Herein, cotton stalk biomass was initially characterized to understand its physicochemical properties as a raw material for biochar production. Furthermore, thermal analysis was conducted using thermogravimetric analysis (TGA), and the results were further utilized to evaluate the cotton stalk's kinetic behavior under thermal decomposition in an inert environment. Advanced kinetics and technology solutions (AKTS) software was for the first time employed to compute the kinetic parameters of cotton stalk pyrolysis, as well as provide kinetic predictions under isothermal conditions. Three methods were used to compute the activation energy ( Ea ) value, namely ASTM‐E698, Flynn‐Wall‐Ozawa (FWO), and Friedman's differential iso‐conversional model. The results obtained using the ASTM‐E698 method indicate an activation energy of 127.23 kJ·mol −1 . Furthermore, the FWO method presented an Ea value ranging 35‐250 kJ·mol −1 . The differential iso‐conversional method is the most robust approach as it adequately represents the complex nature of lignocellulosic biomass decomposition, showing an Ea range between 4 and 250 kJ·mol −1 . Based on the differential iso‐conversional method, kinetic predictions under isothermal conditions were provided. The predictions offer valuable insight for industrial‐scale biochar project developers in relation to production throughput optimization. Furthermore, the kinetic parameters obtained can be utilized in process modeling. Abstract : Herein, cotton stalk biomass was initially characterized to understand its physicochemical properties as a raw material for biochar production. Furthermore, thermal analysis was conducted using TGA, and the results were further utilized to evaluate the cotton stalk's kinetic behavior under thermal decomposition in an inert environment. AKTS software was for the first time employed to compute the kinetic parameters of cotton stalk pyrolysis, as well as provide kinetic predictions under isothermal conditions.